2010
DOI: 10.4319/lo.2010.55.2.0639
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin concentration in Daphnia (D. galeatahyalina) from the epilimnion is related to the state of nutrition and the degree of protein homeostasis

Abstract: The function of hemoglobin (Hb), which is a key protein of many species, was analyzed in Daphnia from the field. Temperature and oxygen content; abundance and composition of phytoplankton; and abundance, body, and clutch sizes of the Daphnia assemblage were measured in the epilimnion and around the thermocline of a reservoir for 2 yr. In addition, carbohydrate, lactate, and hemoglobin concentrations were determined in whole Daphnia. In Daphnia from the thermocline, hypoxia‐induced Hb expression was responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In addition, summer conditions with low food availability and high predation pressure seem unfavourable for D. galeata , which shows better performance under spring conditions with high food abundance and low predation pressure (Jankowski & Straile, 2004). In 2005 and 2006, the biovolume of algae smaller than 20 μm, considered suitable food for the daphnids in the Saidenbach Reservoir, amounted to between 0.25 and 0.29 mm 3 L −1 during the period of spring full circulation in April (Schwerin et al. , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, summer conditions with low food availability and high predation pressure seem unfavourable for D. galeata , which shows better performance under spring conditions with high food abundance and low predation pressure (Jankowski & Straile, 2004). In 2005 and 2006, the biovolume of algae smaller than 20 μm, considered suitable food for the daphnids in the Saidenbach Reservoir, amounted to between 0.25 and 0.29 mm 3 L −1 during the period of spring full circulation in April (Schwerin et al. , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Hb crude extracts were obtained from pools of ten individuals per genotype following established protocols (Schwerin, Zeis, Horn, Horn, & Paul, 2010). In brief, after removing adhering water, the pools of animals were weighed on a precision scale (BP 211D; Sartorius) and homogenized in 100 μl of M4 medium and mini complete protease inhibitor cocktail (Roche) using Teflon ® pestles (Kimble Kontes, Sigma Aldrich, Darmstadt, Germany).…”
Section: Haemoglobin Evolutionary and Plastic Responsementioning
confidence: 99%
“…The expression level of hemoglobin was modulated by exposure not only to oxygen deficiency but also to low food availability and kairomone. It may be considered that the different mechanisms explain the observations: the reduction in hemoglobin may be associated with decrease in total protein in the hemolymph (Schwerin et al, 2010), and the enhanced hemoglobin expression with kairomone may be caused by the activity of methyl farnesoate (Daimon & Shinoda, 2013). In addition, the fitness parameters (somatic growth, reproduction and survival) improved under low DO conditions, indicating that hemoglobin synthesis intricately affects the pattern of other phenotypic changes in Daphnia .…”
Section: Discussionmentioning
confidence: 99%
“…Food limitation reduced the hemoglobin expression level in high O 2 conditions even in the presence of kairomone (Table 2 and Figure 3). Schwerin et al (2010) found that hemoglobin concentrations in a Daphnia galeata ‐ hyalina hybrid species complex, sampled from a field population in Saidenbach Reservoir in Germany, showed the minimal value when chlorophyll a concentrations were lower. In addition, their laboratory experiments demonstrated that starvation can reduce concentrations of hemoglobin in Daphnia under high O 2 conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation